Pediatric wheelchair transportation safety: Transit manual wheelchair design guidelines and injury risk of 6-year-old children in a frontal motor vehicle impact. - Ha D (Pediatric Wheelchair Transportation Safety: Transit Manual Wheelchair Design Guidelines & Injury Risk of 6-year-old Children in a Frontal Motor Vehicle Impact, 2004)
Children with disabilities often cannot be seated in standard child seats or automobile seats because of physical deformities or poor trunk and head control. Therefore, when children with disabilities are transported to schools and developmental facilities, they often remain seated in their wheelchairs in vehicles such as school buses and family vans. Children who must travel seated in their wheelchairs are excluded from the protections dictated by the federal and state laws related to child protection in motor vehicle crashes. This dissertation investigated the safety of children in wheelchairs in transit, mainly using computer simulation software. Three pediatric manual wheelchairs were tested with a Hybrid III 6-year-old ATD in accordance with the ANSI/RESNA WC-19 standard. Using sled test data, a computer model representing a Zippie wheelchair seated with a Hybrid III 6-year-old ATD subjected to a 20g/48kph frontal crash was developed and validated in MADYMO. The injury risks of 6-year-old wheelchair occupants in a frontal impact motor vehicle crash was investigated by analyzing sled test data and by using the pediatric wheelchair computer model. The loads imposed on the wheelchair and occupant restraint system under 20g/48kph frontal impact conditions with varying wheelchair setup conditions was also investigated using the computer model. The study results showed that a 6-year-old wheelchair seated occupant may be subjected to a risk of neck and chest injuries in a frontal impact motor vehicle crash. Results also showed that altering wheelchair settings does have impact on kinematics and injury risk of a 6-year-old wheelchair occupant in a frontal motor vehicle crash. Changing wheelchair settings also had impact on wheelchair kinematics and loads imposed on the wheelchair and occupant restraint system. The study results presented in this dissertation will provide guidelines for manufacturers designing pediatric transit wheelchairs, seating, and occupant restraint system. The pediatric wheelchair model developed in this study will provide a foundation for studying the response of a manual pediatric wheelchair and a child occupant in crashes. Moreover, the model will promote the study of associated injury risks for pediatric wheelchair users in motor vehicle crashes.